ZALABARDO, José Luis (2015): Represention and Reality in Wittgenstein’s Tractatus. Oxford: Oxford University Press. - Liz Gutiérrez, Antonio Manuel (Daimon Revista Internacional de Filosofia, 2018)
Reseña del libro de José Luis Zalabardo, Represention and Reality in Wittgenstein’s Tractatus. Oxford: Oxford University Press, 2015.